Development of Mind Mapping To Improve Student’s Speaking Skills Madrasah Aliyah Hassanudin Gaprang - Sabnisnaini, Alif Muhmmad; Saifudin, Ahmad; Makrifah, Istina Atul (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
The purpose of this study is to the process and results of using mind mapping media to determine the development of English speaking skills of class XII MA Hassanudin Gaprang students in describing a text. English is an international language that must be learned in this modern era. Utilizing media as a strategy in learning is very effective in seeing student development. Using the ADDIE model method in this study, which is known as Research and Development (R & D). Data taken through observation, Interview, and questionnaires. The researcher obtained a value from the Instrument validator of 83% with valid criteria, 75% for the material validator with valid criteria, and the media validator obtained a value of 83.82% with valid criteria.